Implantation of medical housing at Faculdades Nova Esperança as na instrument for health promotion and quality of life (Research, Society and Development, 2021)
Plants with medicinal purposes are part of the great biodiversity, and are introduced in the life of the population since the most remote times and can be used to cure an illness due to their great phytotherapeutic importance, low cost, and easy access. The consumption of herbal products is constantly increasing, as are the customs and principles that have been passed down from generation to generation. It was based on these factors that the present work is the project for the implementation of the medicinal plants garden at Faculdades Nova Esperança, which aims to maintain living examples of medicinal plants, to spread scientific knowledge about the active principles present in these plants, considering that the incorrect use of these herbal medicines can cause not the improvement, but the worsening of the health of those who use them, in addition to developing educational activities through lectures, booklets, workshops, and donation of therapeutic seedlings using recyclable material. The medicinal plant garden was implemented in the Farm School of the Institution in 2019, with 30 medicinal plant species, and is being used as a learning tool in the formation of students, aiming at the use of phytotherapy as a preventive, curative, and therapeutic health practice, adding incentive to the cultivation and correct consumption of these important plant species.